2016
DOI: 10.1111/jmft.12168
|View full text |Cite
|
Sign up to set email alerts
|

Nonviolent Resistance: Helping Caregivers Reduce Problematic Behaviors in Children and Adolescents

Abstract: In this review, the principles of nonviolent resistance (NVR) and studies examining its acceptability and efficacy are reviewed. Originating in the sociopolitical field, NVR has been adapted for numerous settings including parents of youth with externalizing and other problems, foster parents, teachers and school personnel, and caregivers of psychiatric inpatients. NVR has also been applied to reduce accommodation of highly dependent adult children and to improve novice driving habits. The principles of NVR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…Evidence base for NVR NVR has a growing evidence base demonstrating effectiveness in reducing parental helplessness and childhood behaviour problems (Omer and Lebowitz, 2016). One controlled trial of forty-nine families in Israel found evidence that NVR reduced self-reported helplessness and permissiveness in parents of children with a range of behavioural problems, with parents also reporting significant reductions in problem behaviours at one-month follow-up (Weinblatt and Omer, 2008).…”
Section: © 2019 the Association For Family Therapy And Systemic Practicementioning
confidence: 99%
“…Evidence base for NVR NVR has a growing evidence base demonstrating effectiveness in reducing parental helplessness and childhood behaviour problems (Omer and Lebowitz, 2016). One controlled trial of forty-nine families in Israel found evidence that NVR reduced self-reported helplessness and permissiveness in parents of children with a range of behavioural problems, with parents also reporting significant reductions in problem behaviours at one-month follow-up (Weinblatt and Omer, 2008).…”
Section: © 2019 the Association For Family Therapy And Systemic Practicementioning
confidence: 99%
“…NVR has developed from the use of non‐violent and non‐escalatory interventions in the socio‐political field and is concerned with addressing violent behaviour of children towards their parents. The main principles of NVR are described as ‘refraining from violence, reducing escalation, utilizing outside support, and maintaining respect for the other’ (Omer and Lebowitz, : p.688). NVR acknowledges the societal aspect to violence and so interventions require consistent positive action to be used by the whole personal and professional network around the child through the ‘systematic mobilisation of support’ (Weinblatt and Omer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents' problematic behaviors may result in academic failure, physical or psychological harms, and even social issues [1,2]. The Project P.A.T.H.S.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence has been widely considered as a risky developmental period marked by the emergence and escalation of problematic behaviors, such as substance abuse, selfharm and suicide, and unhealthy lifestyles [1,2]. In Hong Kong, adolescent developmental issues such as mental health problems deserve public concern [3, 4].…”
Section: Introductionmentioning
confidence: 99%